2010
DOI: 10.1590/s0104-07072010000100004
|View full text |Cite
|
Sign up to set email alerts
|

Privacidade física referente à exposição e manipulação corporal: percepção de pacientes hospitalizados

Abstract: Estudo descritivo utilizando Análise de Conteúdo, que objetivou descrever a percepção de privacidade física do paciente hospitalizado referente à exposição e manipulação corporal. Participaram 34 pacientes internados e após análise das entrevistas emergiram quatro categorias temáticas, fundamentadas em teorias da privacidade: dignidade e respeito, intimidade e toque, espaço pessoal e territorial, autonomia. Os pacientes admitem desconforto e constrangimento ante a nudez e toque corporal, sobretudo nas partes í… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0
13

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(37 citation statements)
references
References 11 publications
1
23
0
13
Order By: Relevance
“…In agreement with the findings of the present study regarding the gender of the health professional, two studies identified user preferences by same-sex caregivers 6,18 . Souza and Brandão 17 also interviewed 20 patients hospitalized in medical surgical wards in a medium-sized hospital in a municipality in the state of Goiás, stating that the interviewees reported unpleasant experiences regarding the care performed by a professional of the opposite sex.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In agreement with the findings of the present study regarding the gender of the health professional, two studies identified user preferences by same-sex caregivers 6,18 . Souza and Brandão 17 also interviewed 20 patients hospitalized in medical surgical wards in a medium-sized hospital in a municipality in the state of Goiás, stating that the interviewees reported unpleasant experiences regarding the care performed by a professional of the opposite sex.…”
Section: Discussionsupporting
confidence: 91%
“…However, it is difficult to establish limits between the rights of users and the need for professionals to intervene, since touching the body and obtaining information during care are medical needs, but they can hurt users' rights depending on how such interventions occur 6 .…”
Section: Privacy and Confidentiality Of Users In A General Hospitalmentioning
confidence: 99%
“…Os níveis de evidência encontrados nos estudos analisados de acordo com o Joanna Briggs Institute (10) foram o nível 2 (8) , nível 3 (5,7,11) e nível 4 (4,12,13,16,17) .…”
Section: Resultsunclassified
“…O hospital constitui um ambiente hostil à natureza humana pois potencia a fragilidade fí-sica e a vulnerabilidade do doente (4) . Desde há muitos anos que o respeito pela privacidade e confidencialidade do doente é tida como uma obrigação dos profissionais de saúde e na atualidade esta temática continua a ter lugar de destaque na prática dos cuidados (5) .…”
Section: Introductionunclassified
“…With regard to privacy, in fact, it is a necessity and human right for the preservation of his body, exposure and handling by another individual, and disrespect this right features its invasion. In this regard, the Code of Ethics of Nursing Professionals (CEPS), in Article 19, mentions that it is the duty and responsibility of nurses to respect modesty, privacy and intimacy of human beings [35].…”
Section: Discussionmentioning
confidence: 99%